Factor structure and item response of psychosis symptoms among Kenyan adults - Jaguga, F; Ametaj, A; Kim, HH; Stroud, RE; Newton, CR; Kariuki, SM; Kwobah, EK; Atwoli, L; Gelaye, B; Korte, KJ (Elsevier, 2022)
Background The aim of this study was to evaluate the construct validity of the psychosis module of the Mini International Neuropsychiatric Interview version 7.0.2 (MINI-7). Method We utilized data collected from 2738 participants with a primary psychotic or bipolar disorder. Participants were drawn from two Kenyan sites of a large multi-center neuropsychiatric genetic study. The factor structure of the MINI-7 psychosis items were explored using confirmatory factor analyses (CFA) and Item Response Theory approach, for the full sample and by gender. Results The CFA revealed that a 1-factor model provided adequate fit for the MINI-7 psychosis items for the full sample (x2 = 397.92, df = 35, p < .0001; RMSEA = 0.06; CFI = 0.92; TLI = 0.90) as well as for the female (x2 = 185.16.92, df = 35, p < .0001; RMSEA = 0.06; CFI = 0.93; TLI = 0.91) and male groups (x2 = 242.09, df = 35, p < .0001; RMSEA = 0.06; CFI = 0.92; TLI = 0.89). Item thresholds for the full sample, and female and male groups were highest for 'odd beliefs' (-1.42, -1.33, and -1.51 respectively) and lowest for 'visual hallucinations' (-0.03, -0.04, and -0.01 respectively). Limitations Our study used a hospital-based population, which may have excluded patients with milder psychotic symptoms. Findings may therefore not be generalizable to the community setting. Conclusions Our findings indicate good construct validity of the MINI-7 psychosis module, and provides support for use of the tool in diagnosing psychotic disorders in clinical settings in Kenya.